Draft genome sequence of freshwater-derived streptomyces sp. strain BPSDS2, isolated from damte stream, northeast India - Zothanpuia; Passari, Ajit Kumar; Deka, Vinay; Rajput, Lakshmi P. M.; Priya, Purbajyoti; Dharne, Mahesh; Dastager, Syed; Mathew, Oommen K.; Hashem, Abeer; Abd_ Allah, Elsayed Fathi; Singh, Bhim Pratap (American Society for Microbiology, 2019)
We report the draft genome sequence of Streptomyces sp. strain BPSDS2, isolated from freshwater sediments in Northeast India. The draft genome has a size of 8.27 Mb and 7,559 protein-coding sequences.